Answer:
A∩(A∪B)=A
Step-by-step explanation:
Let's find the answer as follows:
Let's consider that 'A' includes all numbers between X1 and X2 (X1≤A≥X2), and let's consider that 'B' includes all numbers between Y1 and Y2 (Y1≤B≥Y2). Now:
A∪B includes all numbers between X1 and X2, as well as the numbers between Y1 and Y2, so:
A∪B= (X1≤A≥X2)∪(Y1≤B≥Y2)
Now, A∩C involves only the numbers that are included in both, A and C. This means that 'x' belongs to A∩C only if 'x' is included in 'A' and also in 'C'.
With this in mind, A∩(A∪B) includes all numbers that belong to 'A' and 'A∪B', which in other words means, all numbers that belong to (X1≤A≥X2) and also (X1≤A≥X2)∪(Y1≤B≥Y2), which are:
A∩(A∪B)=(X1≤A≥X2) which gives:
A∩(A∪B)=A